Pemberdayaan Ekonomi Masyarakat Melalui Gerakan Sejuta Koin NU - Amiruddin, Moh.; Maulaniam Sholah, Hanif (Lembaga Penelitian, Pengembangan dan Pengabdian Kepada Masyarakat (LP3M), 2021)
Through religious figures, the administrators of Nahdlatul Ulama, people of Sindurejo village conveyed some aspirations in the FGD forum (Focus Group Discussion) which is held by KKN (lecturing based on the real social condition) students. One of the problems discussed is about poverty alleviation and alms distribution. Based on those problems, the Community Service team from IAI Al-Qolam which consists of lecturers and students tried to offer a program initiated by the Nahdlatul Ulama Organization through LAZISNU (Lembaga Amil Zakat Infaq and Sedekah) in the form of an NU Coin Box. NU coin box is a community independence program to collect alms and zakat, it’s managing for community who are in need. By this program, hopefully Sindurejo residents will be greatly assisted in distributing alms and zakat through trustworthy institutions. As for less fortunate residents to be slightly helped to improve their economy. The first Coin Box been collected was around Rp. 4,000,000. The target of this program are: NU Care, NU Dakwah and NU Smart. The NU Care program includes compensation for death, sickness compensation and disaster compensation. The amount of compensation for death and illness are Rp. 200,000. As for disaster compensation, it adjusted by the level of economic loses conditions. While, the NU Dakwah program includes assistance for organizational strengthening and Banom. The organizations and Banoms referred to Ranting, Fatayat and Muslimat. Support for Ranting NU is Rp. 200,000, while for the Muslimat and Fatayat are Rp. 150,000 per each. The NU Smart program includes assistance for TPQ (Al-Qur’an learning education for kids). The amount of TPQ assistance is Rp. 15,000 per each for all throughout the Sindurejo area. The program has been warmly welcomed by the community because residents can see the results of their charity directly.